Potentiometric Electronic Tongue for Taste Assessment of Ibuprofen Based Pharmaceuticals. Issue 10 (31st July 2019) - Shishkanova, Tatiana V.; Broncová, Gabriela; Skálová, Annemarie; Prokopec, Vadym; Člupek, Martin; Král, Vladimír
Abstract: The flavor aspect of pharmaceutical formulations is very important in terms of their acceptability for the patient. This work is aimed at using of a novel promising type of electronic tongue (ET), consisting of a potentiometric sensor array, for the discrimination and assessment the taste of commercial pharmaceuticals based on ibuprofen (Ibuflam 4 %). The sensor array was formed by six ion‐selective membranes (ISMs) based on both specific and non‐specific active components. Analysis of potentiometric signal outputs including statistical data processing utilizing the principal component analysis (PCA) method allowed evaluating the role of individual active components of the ISMs in the sense of taste control of the pharmaceutical preparation Ibuflam 4 % before and after flavoring. The sensing array can be used to identify differences in flavor within individual batches from the same producer, since ISMs provide a different response to all components present in the analyzed pharmaceutical. The ET contains ISMs which are able to recognize the bitter taste in the framework of the batches of ibuprofen based pharmaceuticals. To recognize bitter taste, it was essential to include ISMs, providing a response to a particular type of taste, namely, specific and non‐specific ISMs. The experimental findings show that taste‐sensing potentiometric sensor system can be a good alternative to the human panel and is able to detect the slight changes in taste. Abstract :